2017
DOI: 10.1002/ijc.30824
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes, adiposity and cancer morbidity and mortality risk taking into account competing risk of noncancer deaths in a prospective cohort setting

Abstract: Type 2 diabetes (T2D) and adiposity associate with increased risk of several cancers, but the impact of competing risk of noncancer deaths on these associations is not known. We prospectively examined participants in the Malmö Diet and Cancer Study aged 44–73 years with no history of cancer at baseline (n = 26,953, 43% men). T2D was ascertained at baseline and during follow‐up, and body mass index (BMI) and waist circumference (WC) at baseline. Multivariable cause‐specific hazard ratios (HR) and subdistributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Herein, we have demonstrated that HCC rates have not only plateaued but have significantly declined between 2011 and 2016. Although to our knowledge the reasons for the decline in HCC rates are not clear, factors that may have had an effect include halting the spread of hepatitis C virus (HCV) via testing of the blood supply, improvements in HCV treatment, and competing mortality risks . However, of these potential factors, it should be noted that direct‐acting antiviral (DAA) therapy for HCV was not approved by the US Food and Drug Administration until 2011 and the all‐oral DAA combinations were not available until 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we have demonstrated that HCC rates have not only plateaued but have significantly declined between 2011 and 2016. Although to our knowledge the reasons for the decline in HCC rates are not clear, factors that may have had an effect include halting the spread of hepatitis C virus (HCV) via testing of the blood supply, improvements in HCV treatment, and competing mortality risks . However, of these potential factors, it should be noted that direct‐acting antiviral (DAA) therapy for HCV was not approved by the US Food and Drug Administration until 2011 and the all‐oral DAA combinations were not available until 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies were excluded if they had retrospective case–control or cross-sectional design. In case of studies that did not provide sufficient information to calculate effect sizes, corresponding authors were contacted, and of those, two studies provided additional data from their studies 33 , 34 . Two authors (SS and Sh A) independently screened the title and abstract of all articles retrieved.…”
Section: Methodsmentioning
confidence: 99%
“…Its increased morbidity and mortality rates all over the world decrease the quality of human being's lives and productivity even in the developed countries. As a result, it is considered one of the challenging diseases in the pharmaceutical world [4,5]. Currently, available therapeutic agents for DM include insulin and various oral antidiabetic drugs such as glinides, sulfonylureas, and biguanides; most of them have a number of harmful side effects; for this reason, the investigations of safer and effective hypoglycemic medications is one of the essential areas of research [6].…”
Section: Introductionmentioning
confidence: 99%